Hardiness, Perseverative Cognition, Anxiety, and Health-Related Outcomes: A Case for and Against Psychological Hardiness. Issue 6 (December 2019) - Kowalski, Christopher Marcin; Schermer, Julie Aitken
The present study investigates the utility of psychological hardiness as well as the differences between rumination and worry. Undergraduate students completed questionnaires assessing hardiness, worry, rumination, mindfulness, neuroticism, anxiety, somatization, coping, and health. Correlations and partial correlations controlling for neuroticism were examined. Hardiness was negatively correlated with neuroticism, rumination, worry, and anxiety and positively correlated with mindfulness, coping, and health. When neuroticism was statistically controlled, the relationships between hardiness and rumination, health, and coping became nonsignificant, and the relationships between hardiness and worry, mindfulness, and anxiety, although attenuated, remained significant. Rumination and worry were positively correlated, but when neuroticism was statistically controlled, this relationship became nonsignificant. The results suggest that hardiness is better conceptualized as a personality style that contributes to psychological well-being. Furthermore, our findings suggest that rumination and worry are distinct cognitive processes.